The Place of Spirituality and Its Manifestation in Higher Education Literacy Classroom - Flandez-Paycana, Marivel (International Journal of Qualitative Research, 2024)
So much variation in the meaning of spirituality has contributed to the difficulty in pinpointing how spiritual beliefs and values manifest themselves in the classroom. Thus, this study aimed to bridge the gap by exploring the views of faculty members on spirituality and how it manifests in the classroom using the qualitative phenomenological research tradition. In-depth interview data from twelve (12) educators and their selected students were analyzed using the conventional content analysis approach. The key findings of this study were that spirituality is something deep, personal, and relational. It serves as their guiding principle—a value system that is practical in life. It influences the values that teachers emphasize in class, the choice of materials to be used, topics and issues to be discussed, and the level of care and support they give to the students. While spirituality is covert and implemented in subtle and indirect ways in the classroom, both teachers and students agree that spirituality must not be ignored; rather, it must have a place in academia, serving as a powerful source of motivation for both teachers and students. This is an area that should be further explored in the academic context.